Frenectomy in Aberrant Frenulum Labialis – Literature Review - Putri, Tania Fatimah; Sulistiawati; Mozartha, Martha (Sriwijaya Journal of Dentistry, 2024)
A smile is a human facial feature that is attractive and one of the forms of human communication and expression. An esthetic smile is determined by several factors such as the shape, position, and color of the teeth, as well as the condition of the frenulum labialis. Aberrant frenulum labialis can be treated by performing a frenectomy. Properly diagnosing and planning the management of aberrant frenulum must be done to achieve satisfactory results both in healing and aesthetics. This literature review is a compilation of an overview of the frenulum and its classification of attachments, indications and contraindications for frenectomy, and various techniques of frenectomy.